PENINGKATAN KEMAMPUAN MENULIS PENGALAMAN PRIBADI DALAM CATATAN HARIAN MELALUI MEDIA KOMIK PADA SISWA KELAS VII A SMP NEGERI 11 MANOKWARI TAHUN AJARAN 2016/2017 - Kamodi, Paulina; Warami, Hugo; Tulalessy, Quin D. (JURNAL TRITON PENDIDIKAN, 2017)
The research entitles: “The Improvement Of Writing Ability Through Personal Experience In Dairy Of Comic Of StudentsAt Grade VII A SMP Negeri 11 Manokwari Academic Year 2016/2017”, the research problems are: (1) how was the abilityin students dairy before using comic, (2) can comic as a media improve the personal experience writing ability in a dairy.The research method are quantitative and qualitative. The research is a classroom action research, consisting of four stages:Planning, implementation, observation, and reflection.Based on the research of pra-cicle, out of 39 students, 3 students (7,69%) get 85-100 grades and categorized as very satisfactory,10 students (25,64%) get 75-84 and categorized as satisfactory, 10 students (25,64%) get 65-74 and categorized as everage,16 students (41,03%) get below 65 and categorized as unsatisfactory. Then, in cicle I, 2 students are categorized as verysatisfactory (5,13%), 6 students are categorized as very satisfactory (15,38%), 2 students are categorized as everage (5,13%), 29students are unsatisfactory (74,36%). In cicle II, out of 39 students, 10 students are very satisfactory (25,64%), 13 studentsare satisfactory (33,33%), 11 students are everage (28,20%), 5 students are unsatisfactory (12,82%).The research shows that comic as a media can increase the writing ability of students of grade VII A SMP Negeri 11 Manokwariin writing their personal experience in their dairy.